O ensino de história e cultura afro-brasileira nos livros didáticos utilizados na região da AMESC (1980-2018) - Copetti, Edilene dos Santos (2019)
The enslaved worker has become the main labor force in sugarcane, tobacco, cotton plantation, etc., in the villages and cities, in the mines, in the cattle farms and in the huge coffee enterprise, since the century XVI. His contributions beyond economic issues are witnessed in dance, music and language. Rare are the aspects of our culture that haven’t been shaped with the help of African and Afro-Brazilian hands and intelligence. It is proposed, then, to reflect on Law 10.639 / 03, which made it compulsory to teach Afro-Brazilian and African history and culture in all public and private schools, from elementary to high school. Also, to make an analysis of the law and if this is contemplated in the textbooks, in other words, to check if there was, in fact, alteration of the contentes, as was required by the law. If they sustain a change in the perspective of the look that the teaching of History gave the Afrodescendents, showing a greater visibility to this group so silenced in Brazilian history. To answer these questions it was necessary to carry out bibliographical research; definition of basic concepts: slavery, curriculum, Law 10.639 / 03, abolition, textbook, etc .;systematization and organization of the readings that were made and analysis of textbooks. These analyzes were made in High School’s History textbooks, in a specific area that involves the state public schools that belong to the Association of Municipalities of Extremo Sul Catarinense, AMESC. The analyzes were made in didactic books published before the law, therefore 2003 and after that. Through the analyzes, it can be affirmed that the Law 10.639 / 03 brought a significant improvement to the didactic material available in schools, in comparison to the years prior to the implementation of the law. However, the simplification of some themes was noted, and the due importance is not been given to some issues that, addressed in another way, would change thoughts so deeply rooted that reproduce stereotypes and prejudices about Africa and Africans, marginalizing the movements of resistance.